The Effect Of Processed Snakefish (Channa Striata) On The Healing Process Of Diabetes Mellitus Ulcers - Resti, Resti; Indah Lestari; Erick Gamaliel; Pratiwi Nasir; Fadil Mula (Jurnal EduHealth, 2025)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion , insulin action or both . The increase in the number diabetes mellitus sufferers causes an increase in the incidence diabetes mellitus complications , one of which is wounds on the feet of diabetic foot ulcers . In the wound healing process in diabetes, there are many factors that are often forgotten , one of which is adequate nutrition . Fulfilling this nutrition is very important because it can influence the wound healing process . apart from fulfilling nutrition , wound care also needs to be paid attention to . Snakehead fish ( Channa striata ) is a freshwater fish that is commonly used by Indonesian people as an Ingredients for healing wounds . . The main ingredients in this fish are relatively high protein and albumin. The albumin content in this fish is a globular protein which is often used clinically to improve nutrition and the wound healing process . Albumin also help in the process of forming body tissue . This literature aiming to determine the effect of providing processed snakehead fish ( Channa Striata ) on the healing process diabetes mellitus ulcers . The method used is a literature review with a Narrative Reviews design to identify and summarize previously published articles regarding the Effect of Providing Processed Snakehead Fish ( Channa Striata ) on the Healing Process of Diabetes Mellitus Ulcers . From the 10 articles summarized , the results showed that processed snakehead fish ( Channa striata ) contains protein, albumin, carbohydrates , fat and Zn which help in the healing process of diabetic ulcer and can reduce blood glucose levels .